Drug targeting in cancer therapy - Nys, L.; Raeuschl, P.; Ess, S.; Nestelbacher, R.; Joubert, I.A.; Geppert, Μ.; Himly, M. (Open Schools Journal for Open Science, 2020)
Drug targeting enables the local reslease of medication at the desired site or organ. This ensures that the drug asserts its effects focused to a small site, minimising systematic side effects. Drug targeting has been successfully applied in cancer therapy and can be performed actively or passively. During passive drug targeting, carriers containing the active cancer drug concentrate within the tumour tissue due to increased blood circulation and vascular permeation (enhanced penetration retention principle). Active drug targeting on the other hand, facilitates ligand-recepto interacions.